2003
DOI: 10.1097/01.asn.0000045046.94575.96
|View full text |Cite
|
Sign up to set email alerts
|

Bioartificial Kidney Ameliorates Gram-Negative Bacteria-Induced Septic Shock in Uremic Animals

Abstract: Abstract. The bioartificial kidney (BAK) consists of a conventional hemofiltration cartridge in series with a renal tubule assist device (RAD) containing 10 9 porcine renal proximal tubule cells. BAK replaces filtration, transport, and metabolic and endocrinologic activities of a kidney. Previous work in an acutely uremic dog model demonstrated that BAK ameliorated endotoxin (lipopolysaccharide [LPS])-induced hypotension and altered plasma cytokine levels. To further assess the role of BAK in sepsis in acute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 47 publications
1
65
0
1
Order By: Relevance
“…In vitro and ex vivo tests of renal assist devices have been conducted of animals and critically ill patients, with promising results that include better cardiovascular and hemodynamic parameters and improved survival (18 -20). Of particular interest is the potential differential beneficial effect in patients with acute kidney injury associated with sepsis (21)(22)(23)(24)(25).…”
Section: Living Membranes and Bioartificial Kidneymentioning
confidence: 99%
“…In vitro and ex vivo tests of renal assist devices have been conducted of animals and critically ill patients, with promising results that include better cardiovascular and hemodynamic parameters and improved survival (18 -20). Of particular interest is the potential differential beneficial effect in patients with acute kidney injury associated with sepsis (21)(22)(23)(24)(25).…”
Section: Living Membranes and Bioartificial Kidneymentioning
confidence: 99%
“…A series of additional animal experiments investigated the impact of treatment with this device on the high mortality of sepsis complicated by AKI. Studies in both dogs and pigs have demonstrated that RAD treatment in a bioartificial kidney circuit improves cardiovascular performance associated with changes in cytokine profiles and confers a significant survival advantage in septic or endotoxin animal models [13,14,15]. …”
Section: Preclinical Studies Of Bioartificial Kidneymentioning
confidence: 99%
“…In terms of augmentation of traditional hemodialysis, a "renal assist device," which is composed of a membrane coated with cultured porcine proximal tubule cells, has been developed (14,15). These cells support unidirectional transport, and when added in series to a traditional hemofiltration circuit, the resultant bioartificial kidney appears to significantly improve outcomes of acutely uremic dogs in models of endotoxin-mediated sepsis (10). Human trials are in progress.…”
Section: Cell-based Strategiesmentioning
confidence: 99%